DECOLONIZING FREEDOM OF INFORMATION RESEARCH: WHAT IS KNOWLEDGE OR WHAT IS TRUTH? (Canadian Journal of Native Studies, 2026)
The relationship between Canadian state agencies and FirstNations, Inuit, and Métis peoples has long been one of control,domination, and exploitation. Research on this relationship cancontribute to decolonization by revealing how Canada exercisesstate colonial power, and conversely, how such power has beenresisted. One tool that has been used in this type of research isFreedom of Information (FOI) and Access to Information (ATI)requests. FOI and ATI requests are used to obtain governmentinformation and records and are increasingly used in social scienceresearch. The ability for FOI researchers to make requestsstrengthens the credibility of their work while serving as anexercise in empowerment by accessing information otherwiseguarded by institutions. We sought to answer two questions:(1) How can FOI/ATI requests be used to decolonize research,and (2) What does it mean for ethics and critical research toview FOI/ATI requests in this way, particularly for settler researchers?Both questions were answered by examining existingliterature that used FOI/ATI requests in their research onCanadian state agencies that govern First Nations, Inuit, andMétis peoples.